Comparative proteomic study of pig muscle proteins during growth and development of an animal - A. G. Akhremko; E. S. Vetrova (Теория и практика переработки мяса)
The production of high-quality pork is closely related to the growth and development of muscle tissue. The present article provides a comparative proteomic research of l. dorsi, b. femoris, m. brachiocephalicus during the pigs’ growth and development (at age of 60 days and 180 days). This work was supported by data of electrophoretic methods: one-dimensional electrophoresis according to Laemmli with densitometric assessment in the ImageJ software and two-dimensional electrophoresis according to O’Farrell method with its further processing on the software ImageMaster. The mass spectrometric identification was conducted with the help of the high-performance liquid chromatography (HPLC) system connected to a mass spectrometer; further the data were interpreted by search algorithm Andromeda. When comparing frequency diagrams of one-dimensional electrophoregrams of all three muscle tissues of weaned pigs, the greatest difference was observed for the muscle sample l. dorsi. Comparison of diagrams of muscle tissue samples taken for mature pigs showed a great similarity of all three studied muscles samples. Within the framework of the research, the Fold indicator was calculated. The exceeding its value by more than 2 units is generally considered to be a statistically significant difference. When analyzing two-dimensional electrophoretograms of weaned pigs’ muscles, 18 protein fractions were revealed with Fold > 2. When examining the muscle tissue of mature pigs, 15 of those proteins were found; the differences were mostly detected in the minor protein fractions. The mass spectrometric analysis of the cut bands with well-pronounced differences from the onedimensional electrophoretogram revealed 214 proteins involved to a greater extent in cellular and metabolic processes, physical activity and localization. Growth and development protein — semaphorin‑6B (96.78 kDa) — was revealed in muscle tissue of l. dorsi, a. Also in l. dorsi and b. femoris the growth and development proteins were found: cadherin‑13 (78.23 kDa), cadherin‑7 (87.01 kDa), the F‑actin-cap protein beta subunit (30.66 kDa), and two uncharacterized proteins at 65.60 kDa and 63.88 kDa.